Professionals’ Perceptions of Female Child Sexual Offenders - Christensen, Larissa S. (Journal of interpersonal violence, 2021)
The aims of the current study were to (a) obtain an in-depth understanding about professionals’ perceptions of female child sexual offenders and (b) identify where system efforts should be focused to better address and acknowledge female child sexual offenders. In-depth semistructured interviews were conducted one-on-one with a diverse group of professionals (police officers, social workers, counselors, case managers, child and family support workers, and a legal professional; N = 21) involved in the community response and justice sector, which allowed for unique views across diverse vantage points. Four core themes were identified through thematic analysis: (a) female child sexual offenders are a heterogeneous group, (b) negative impact of female-perpetrated sexual abuse, (c) gender of perpetrator is predominantly insignificant in case dealings, and (d) the need for a more open discourse on female child sexual offenders. Professionals in the current study acknowledged that female child sexual offenders can inflict serious and persistent negative impacts on victims and that the gender of the offender is insignificant in their individual professional dealings of child sexual abuse cases. While these findings appear to be a positive step forward, away from earlier perceptions identified in the literature, it was evident that the gender of the perpetrator may still play a significant role in some dealings across professions and among colleagues. Two areas identified by professionals as requiring system efforts were (a) professional development along with the dissemination of appropriate research to better inform professionals and (b) the need for a more open discussion in society concerning female-perpetrated sexual abuse. The findings of the current study may assist with appropriate recognition, protection, and intervention for victims of female-perpetrated sexual abuse.